Physical Condition Analysis Report for NPCI West Kalimantan Province Athletes - Rahmat Putra Perdana (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objectives. The primary objective of this study is to assess the level of explosive power and leg strength among the athletes who have undergone training under the Indonesian National Paralympic Committee (NPCI) in the West Kalimantan Province. The research aims to provide an in-depth analysis of the physical abilities of these athletes, with a particular focus on their lower body strength and explosive power. Materials and Methods. In this particular study, a total of 26 male and female athletes were selected, who were being coached by NPCI West Kalimantan. These selected individuals were then subjected to leg explosive power testing, while 27 of them underwent leg strength testing. To ensure the accuracy of the results, a quantitative descriptive research method was employed. The researchers utilized two different data collection techniques, including Standing Long Jump and Back and Leg Dynamometer tests, which allowed them to accurately measure and evaluate the physical abilities of the athletes. Results. According to the findings of a recent study, the explosive leg strength ability of 26 male and female disabled athletes has been evaluated, and the results indicate that the average value of such ability is categorized as Poor. Similarly, the study also evaluated the leg strength ability of 27 male and female disabled athletes, and the average value of this ability was found to be in the Poor category as well. These results suggest that there is significant room for improvement in terms of developing leg strength among disabled athletes. Conclusions. Sports organizations, coaches, and athletes can benefit significantly by knowing the explosive power and leg strength of an athlete. This information can serve as a valuable benchmark and evaluation material to assess an athlete's physical abilities and identify areas where they need improvement. Additionally, such knowledge can help in designing training programs that focus on specific areas of an athlete's body that require strengthening. This approach is especially valuable in the case of athletes with disabilities, as it can help them improve their sports performance and achieve their full potential. By incorporating data on explosive power and leg strength in their training plans, coaches and sports organizations can help athletes with disabilities enhance their skills, overcome limitations, and achieve their athletic goals.